The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3348/kjr.2016.17.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Intravenous Leiomyomatosis with Intracardiac Extension and Pulmonary Benign Metastases on FDG PET/CT: A Case Report

Abstract: A 48-year-old woman presented with a 50-day history of irregular vaginal bleeding and lower abdominal pain. Ultrasound indicated an extremely large occupying lesion in the pelvic cavity that was highly suggestive of malignancy. Fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) was performed to further assess the nature of pelvic abnormality. PET/CT images demonstrated a diffusely lobulated mass ranging from cervix up to the inferior pole of kidneys with mild FDG uptake. Simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It was first described by Birch-Hirschfeld in 1896 [3] while IVL with the cardiac extension was first reported in 1907 by Dürck [2,4]. An extrauterine leiomyoma occurs in 30% of cases and IVL with the cardiac extension has been reported in approximately 10% of cases [1]. In 2015, Fornaris et al [2] reported a case of IVL with extension to the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first described by Birch-Hirschfeld in 1896 [3] while IVL with the cardiac extension was first reported in 1907 by Dürck [2,4]. An extrauterine leiomyoma occurs in 30% of cases and IVL with the cardiac extension has been reported in approximately 10% of cases [1]. In 2015, Fornaris et al [2] reported a case of IVL with extension to the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
“…An IVL is a rare [1] and potentially life-threatening tumor [2]. It was first described by Birch-Hirschfeld in 1896 [3] while IVL with the cardiac extension was first reported in 1907 by Dürck [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all three entities are rare, intravenous extension into the heart is the most common, with more than 100 reported cases since the early 1900s [2], and the least reported type is benign metastasizing leiomyoma It is not excluded, without being proven, that their physiopathology is common [14,15]. Furthermore, it is necessary to confirm the diagnosis by histological examination in order to rule out the differential diagnosis of leiomyosarcoma, which may have the same clinical characteristics as benign metastatic leiomyoma [16][17]. To the best of our knowledge, there are only four prior case reports of benign metastasizing leiomyoma to the heart (Table 1) [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Although IVL is histologically benign, the tumor has the potential to be clinically aggressive due to its massive intraluminal growth. In most cases, IVL is limited to the pelvic veins, and in rare instances, may extend through the inferior vena cava (IVC) to the right heart chambers (causing intracardiac leiomyomatosis (ICL) (2). Further intracardiac spread into the main pulmonary artery is potentially life-threatening.…”
Section: Introductionmentioning
confidence: 99%